Twin‐screw reactive extrusion for phosphorylation of pea starch with a retained granular identity. (3rd July 2017) - Huo, Gang; Donner, Elizabeth; Thompson, Michael R.; Liu, Qiang
Abstract : The present work examines the ability to reactively modify a pea starch by phosphorylation in a twin‐screw extruder without the loss of its granular form, in order to produce a product for functional food uses. This reaction was studied by varying formulation variables of moisture content as well as reactant and sodium sulfate concentration at 95°C and 150 rpm. The modified starch was characterized for its phosphorus content, in vitro digestibility by the Englyst method, thermal gelatinization properties, and pasting behavior. Phosphorus contents of intact starch granules as high as 0.3% were found (close to the 0.4% limit for foods), produced continuously under extrusion conditions corresponding to a residence time of approximately one minute. Higher moisture content and low sodium sulfate concentration favored higher phosphorus content but increased the chances of amylose leaching and agglomerating of the exiting granules. In all cases, the pea starch experienced some change in its gelatinization transition consistent with simultaneous heat‐moisture treatment occurring along with the reaction inside the extruder. The current configuration of the process was not found suitable to major increases in resistant starch content though minor improvements in slowly digestible starch content were reported.